2007
DOI: 10.4049/jimmunol.178.4.2163
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Mammalian Target of Rapamycin in Regulating T Cell Activation versus Anergy

Abstract: Whether TCR engagement leads to activation or tolerance is determined by the concomitant delivery of multiple accessory signals, cytokines, and environmental cues. In this study, we demonstrate that the mammalian target of rapamycin (mTOR) integrates these signals and determines the outcome of TCR engagement with regard to activation or anergy. In vitro, Ag recognition in the setting of mTOR activation leads to full immune responses, whereas recognition in the setting of mTOR inhibition results in anergy. Full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
246
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(254 citation statements)
references
References 37 publications
5
246
0
3
Order By: Relevance
“…We further examined the effects of TSC1 deficiency on mTOR signaling in T cells under activation and anergy conditions. WT naïve CD4 + T cells under anergy-inducing conditions exhibit decreased 4E-BP1 phosphorylation compared with those WT T cells under activating conditions, indicating that mTORC1 signaling is defective in anergic T cells, which was consistent with previous observations (15). However, TSC1-deficient naïve CD4 + T cells displayed elevated 4E-BP1 phosphorylation in both activating and anergy-inducing conditions (Fig.…”
Section: Contribution Of Enhanced Mtorc1 Signaling To the Resistance Ofsupporting
confidence: 82%
See 1 more Smart Citation
“…We further examined the effects of TSC1 deficiency on mTOR signaling in T cells under activation and anergy conditions. WT naïve CD4 + T cells under anergy-inducing conditions exhibit decreased 4E-BP1 phosphorylation compared with those WT T cells under activating conditions, indicating that mTORC1 signaling is defective in anergic T cells, which was consistent with previous observations (15). However, TSC1-deficient naïve CD4 + T cells displayed elevated 4E-BP1 phosphorylation in both activating and anergy-inducing conditions (Fig.…”
Section: Contribution Of Enhanced Mtorc1 Signaling To the Resistance Ofsupporting
confidence: 82%
“…Engagement of the TCR activates both mTORC1 and mTORC2, which is dependent on the RasGRP1-Ras-Erk1/2 pathway and is inhibited by diacylglycerol kinases (11)(12)(13). Rapamycin treatment or genetic ablation of mTOR induces T-cell anergy and inhibits helper T-cell differentiation but promotes expansion of natural regulatory T cells (nTregs) and the generation of inducible Tregs (9,(14)(15)(16). Contrary to its positive role in promoting T-cell activation and effector T-cell function during primary immune responses, mTOR inhibits memory CD8 T-cell formation and function during viral infection (17,18).…”
Section: T-cell Activation | Signal Transductionmentioning
confidence: 99%
“…This increased activation and proliferation of DN T cells correlated with loss of their suppressive capacity. Previous studies linked Akt/ mTOR signaling to an anergic state of T cells by demonstrating that mTOR inhibition promotes T cell anergy (45)(46)(47). Of interest, our findings demonstrated that IL-7 downregulates expression of anergy-controlling factors FOXO, NFAT, p27kip1, EGR, and CBL in DN T cells, suggesting that IL-7/Akt/mTOR signaling abolishes an anergic-like state of the DN T cells.…”
Section: Discussionmentioning
confidence: 52%
“…Cellular composition of plaque might not only influence plaque growth but also its stability. Previous reports in experimental and human atherosclerotic lesions suggest that increased macrophage activities mostly associated with inflammatory processes, extracellular lipid accumulation, or decreased SMC density might be the pathogenic basis for plaque instability 18,19) . Macrophages in the vascular wall can be selectively cleared via the induction of autophages by m-TOR inhibition 20) .…”
Section: Discussionmentioning
confidence: 99%